2020
DOI: 10.1021/acs.jpcc.0c02382
|View full text |Cite
|
Sign up to set email alerts
|

Reversible Symmetry-Breaking Charge Separation in a Series of Perylenediimide Cyclophanes

Abstract: Excited-state symmetry-breaking charge separation (SB-CS) can offer an efficient pathway to solar energy capture and conversion. We synthesized a series of 1,6,7,12-tetrakis­(4-t-butylphenoxy)­perylene­(3,4:9,10)­bis­(dicarboximide) cyclophane dimers with m-xylylene, p-xylylene, and 4,4′-diyldimethane-1,1′-biphenyl spacers and studied them with steady-state and time-resolved optical spectroscopies. Photoinduced SB-CS occurs in all three cyclophanes in CH2Cl2, with the SB-CS rate decreasing as the interchromoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
103
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(113 citation statements)
references
References 55 publications
6
103
0
Order By: Relevance
“…CS state formation involving molecular distortions can accelerate the nonradiative decay of the singlet state and lead to a short-lived CS state. As expected, in many cases, 12,13,18,20,40 the CS state is not emissive and shows a short lifetime. Furthermore, the recombination rate of the CS state becomes faster and faster with the increase in the polarity of the solvent.…”
Section: Resultssupporting
confidence: 80%
See 2 more Smart Citations
“…CS state formation involving molecular distortions can accelerate the nonradiative decay of the singlet state and lead to a short-lived CS state. As expected, in many cases, 12,13,18,20,40 the CS state is not emissive and shows a short lifetime. Furthermore, the recombination rate of the CS state becomes faster and faster with the increase in the polarity of the solvent.…”
Section: Resultssupporting
confidence: 80%
“…It has been found that the SB-CS rate and the recombination rate is strongly sensitive to the electronic coupling between the adjacent molecular units that is determined by the relative inter-/intra-molecular distance and orientation. 13,18–21 For example, Wasielewski group investigated the SB-CS process in cofacial and linear perylene diimide (PDI) dimers and found that ultrafast SB-CS (1/0.52 ps −1 ) could be conducted in cofacial PDI dimer even in weakly polar toluene but with a fast recombination rate (1/222 ps −1 ). 22 Instead, SB-CS cannot proceed in linear PDI dimer in toluene but only in polar solvents.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…121 Such SBCS relaxation processes have indeed been unambiguously proven by the detection of both the PBI radical anion and cation species in transient absorption spectra for the examples shown in Figure 10, with the spacers depicted in green. 122,123 These examples show that a direct π−π contact is not necessarily required and maybe even not favorable because closely π-stacked photoexcited PBI dyes have an increased tendency to relax into excimer states. 118 Because the latter process is typically accompanied by structural relaxation, the SBCS process appears to be most efficient in rigid structures such as cyclophanes that prohibit the deep trapping of the excimer species by structural relaxation.…”
Section: ■ Elucidating Photophysical Processes In Excited Dye Aggregatesmentioning
confidence: 99%
“…Since oxidation of 1c or 3c is not reversible, we could not measure the absorption spectrum of the corresponding PDI˙ + . Nevertheless, PDI˙ + generated from related PDI derivatives 33,34 possess an absorption that matches the observed spectroscopic signature of the generated transient. Hong et al 34 a attributed a similar transient feature at 615 nm to the ME state.…”
Section: Resultsmentioning
confidence: 72%